New species of Neoplecostomus (Neoplecostomini: Loricariidae) lacking adipose fin from upper Rio Paraná basin, central Brazil - Silva, Gabriel S. C.; Reia, Lais; Zawadzki, Cláudio H.; Roxo, Fabio F. (Zootaxa, 2019)
In the present study, we describe a new species of Neoplecostomus from central Brazil. The new species is known from Córrego Cachoeira a right tributary of the upper Rio Paraná basin. It can be distinguished from all congeners by absence of adipose fin or azygous plates on the dorsum surface of the caudal peduncle. Additionally, the new species differs from N. botucatu and N. paranensis by having a dark caudal fin with a unique v-shaped hyaline vertical area and a larger lower lip. A discussion on the morphological variation of adipose fin among species of Neoplecostomus is also provided.